2011
DOI: 10.2174/138945011798184155
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention by Targeting the Epigenome

Abstract: The term "epigenetics" refers to modifications in gene expression caused by heritable, but potentially reversible, changes in DNA methylation and chromatin structure. Given the fact that epigenetic modifications occur early in carcinogenesis and represent potentially initiating events in cancer development, they have been identified as promising new targets for prevention strategies. The present review will give a comprehensive overview of the current literature on chemopreventive agents and their influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 314 publications
(362 reference statements)
2
102
0
Order By: Relevance
“…9,10 We have previously reported that isoflavone could alter the miRNA expression profiles, leading to the inhibition of cancer cell growth, induction of apoptosis, reversal of epithelial-to-mesenchymal transition (EMT), and enhancement of efficacy of conventional cancer therapeutics. 11,12 In this study, we investigated whether isoflavone could demethylate DNA sequences in the promoter of tumor suppressive miR-29a and other miRNAs and thus affect the expression of their target genes.…”
Section: Epigenetic Deregulation Of Mir-29a and Mir-1256 By Isoflavonmentioning
confidence: 99%
“…9,10 We have previously reported that isoflavone could alter the miRNA expression profiles, leading to the inhibition of cancer cell growth, induction of apoptosis, reversal of epithelial-to-mesenchymal transition (EMT), and enhancement of efficacy of conventional cancer therapeutics. 11,12 In this study, we investigated whether isoflavone could demethylate DNA sequences in the promoter of tumor suppressive miR-29a and other miRNAs and thus affect the expression of their target genes.…”
Section: Epigenetic Deregulation Of Mir-29a and Mir-1256 By Isoflavonmentioning
confidence: 99%
“…Tumors grew spherically, and their diameters were measured with a hole-mask. Tumor volumes were calculated as (4/3)pr 3 . Animals were sacrificed by cervical dislocation when the tumor diameter reached 25 mm.…”
Section: Xenograft Mouse Modelmentioning
confidence: 99%
“…In particular, the promotion phase is a rate-limiting step in the tumorigenesis process (1), is mostly epigenetically regulated, hence, reversible, and is an attractive target for chemoprevention (3). The JB6-cell model is ideal to study tumor promotion and widely used to identify antitumor promotion agents (4).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hypermethylation status in the promoter regions of tumor-suppressing genes has been demonstrated in various cancers recently, such as estrogen receptor α (ESR1), glutathione S-transferase π1 (GSTP1), retinoid acid receptor β2 (RARβ2), and death-associated protein kinase 1 (DAPK1) in breast cancer; ESR1 and RARβ2 in colorectal cancer; GSTP1 and RARβ2 in prostate cancers; and DAPK1 in lung cancers (2,3).…”
Section: Introductionmentioning
confidence: 99%